Effect of drip irrigated mulch on soil properties and water use efficiency-A review - KUMAR, ROHITASHW; KUMAR, MUKESH (Journal of Soil and Water Conservation, 2020)
The growth and yield of vegetables affect the method of irrigation and different types of mulch. The present study reviewed drip irrigated mulch with different volume of irrigation (V, 0.8V and 0.6V volume), were applied in drip treatments. High soil temperature was developed under transparent mulch as compared to black mulch. Black mulch increased the soil temperature in the root zone by 2.5 to 4Â°C as compared to non-mulched crop plots. The moisture depleted from the non-mulched were more than mulched plots. Water saving obtained by the use of plastic mulch was about 25 to 35% in the different treatments. All treatments with black mulch increased the yield as compared to the control treatment. Drip irrigation along with mulching in vegetable can reduce the cost of cultivation through efficient water management.